ASSOCIATION OF UNDER NUTRITION WITH SEVERITY OF CHILDHOOD ASTHMA - Dr. Saranya K. Murthy; Bindu Krishnan Padma; Nisha Valiyaveetil Krishnan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BackgroundAsthma is one of the common chronic childhood illnesses and the majority of kids affected are having associated poor nutritional status. Undernutrition and hence decreased muscle mass leads to poor functional reserve for respiration, vital capacity and more breathing difficulty. A significant proportion of asthmatic children are found to have associated anaemia also. Understanding of association of undernutrition with asthma helps in optimizing treatment for asthmaObjectiveTo estimate the prevalence of undernutrition among children with asthma and investigate the association of undernutrition with severity of asthma.MethodsA cross-sectional study was done on 471 children with asthma attending the Paediatrics department of Government Medical College, Kottayam. Children with asthma were classified according to their severity and level of control of symptoms according to NAEPP (National Asthma Education and Prevention Program) guidelines using a predesigned questionnaire, detailed history and examination. Children with undernutrition detected on auxological examination in terms of underweight and stunting were categorized using IAP growth charts and anaemia categorized according to WHO based on a complete blood count study and Peripheral smear report. The data was analysed using SPSS 22.ResultsOut of 471 children with asthma, the prevalence of underweight was 35.5%, stunting was 3.6% and anemia was 29.9%. Moderate persistent asthma was found to be significantly more common among children with underweight and stunting (p value 0.031 and